The Use of Audio Visual Media to Improve Student Learning Outcomes in Class X MAN 9 Jombang - Iin Baroroh Ma’arif; Hidayatur Rohmah; A Kanzul Fikri; Serly Amelia (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine the use of audio-visual media can improve student learning outcomes in class X MIA 2 MAN 9 Jombang. This research is a classroom action research. This type of research is to use descriptive qualitative and quantitative methods because this research was conducted with the aim of obtaining student learning outcomes using Audio Visual media. This research model refers to the classroom action research proposed by Kemmis and Mc Taggart models. As well as the lack of participation and enthusiasm of students when participating in class learning. In this case he improvement of learning is carried out. To get solution. This research was conducted at MAN 9 Jombang for the 2022-2023 academic year for class X MIA 2 students. The results of the study were for students who completed cycle I with a percentage of 42,31%. After making improvements to learning in cycle II with a percentage of 88.46%. While student activity in the cycle I with a percentage of 55%, and cycle II with a percentage of 85%. From the results of this study it can be concluded that the use of audio-visual media can improve student learning outcomes in the Aqidah Akhlak class X MIA 2 subject MAN 9 JOMBANG.